2013
DOI: 10.1093/toxsci/kft150
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Mediated Inflammation Leading to EMT via miR-200c Is Involved in Cell Transformation Induced By Cigarette Smoke Extract

Abstract: Cigarette smoking constitutes a major human health hazard because it is the most important risk factor for lung cancer. Although evidence for smoking-induced lung cancer in humans is strong, the molecular mechanisms by which smoking causes cancer remain to be established. In this investigation, we evaluated the roles of inflammation and the epithelial-mesenchymal transition (EMT) in cigarette smoke extract (CSE)-induced transformation of human bronchial epithelial (HBE) cells. The results showed that chronic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 66 publications
(78 reference statements)
7
59
0
Order By: Relevance
“…Interestingly, they also found a higher miR-101 expression in slides of lung tissue samples from COPD patients compared with controls, suggesting that this miRNA may also play a role in COPD pathogenesis [16]. Another in vitro study showed that CSE exposure of human bronchial epithelial cells leads to a decrease in miR-200c expression [17]. This miRNA was suggested to maintain the epithelial phenotype as it was shown to target the expression of the E-cadherin transcriptional repressors ZEB1 and ZEB2 [37,38].…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, they also found a higher miR-101 expression in slides of lung tissue samples from COPD patients compared with controls, suggesting that this miRNA may also play a role in COPD pathogenesis [16]. Another in vitro study showed that CSE exposure of human bronchial epithelial cells leads to a decrease in miR-200c expression [17]. This miRNA was suggested to maintain the epithelial phenotype as it was shown to target the expression of the E-cadherin transcriptional repressors ZEB1 and ZEB2 [37,38].…”
Section: Introductionmentioning
confidence: 94%
“…Compared with the control group, the secretions of inflammatory factors of IL-6, IL-8, and TNF-α were significantly increased in all LPS-treated groups. Now, it is believed that the molecular mechanism of LPS-induced inflammation mainly involves the NF-κB signaling pathway, which may cause acute or chronic inflammation and increase the production of reactive oxygen and nitrogen species and, therefore, result in Toll-like receptor (TLR)-related diseases [16][17][18][19]. Previous studies phospho-NF-B p65/total ratio of our research team investigated the potential antiinflammatory effects of baicalin, and such effects were further confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke is undoubtedly the driver of EMT in smokers and indeed numerous studies have demonstrated that cigarette smoke extract can induce EMT in cultured airway epithelial cells [Veljkovic et al, 2011;Milara et al, 2013;Wang et al, 2013;Zhao et al, 2013;Eurlings et al, 2014;Shen et al, 2014]. However, cigarette smoke is a complicated mixture of chemicals and compounds, and the specific components responsible for EMT induction remain largely unknown.…”
Section: Drivers and Mechanisms Of Emt In Airway Epitheliummentioning
confidence: 99%